ANALISIS HUBUNGAN USIA, PARITAS, DAN KECEMASAN DENGAN INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF - Yusi Revi; Titin Dewi Sartika Silaban; Sri Handayani (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Labor begins with the descent of the head into the pelvic cavity by pressing the nerves that cause pain, and the causes include physiological and psychological factors. Labor pain that doesn't subside can cause discomfort and stress. The data center of hospital associations in Indonesia explained that 15% of women in Indonesia experienced childbirth complications and 22% stated that labor was painful due to severe pain during delivery. In comparison, 63% did not receive information about the preparations to be made. to reduce pain during labor. This study aimed to determine the relationship between age, parity, and anxiety with labor pain intensity in pregnant women. The method used in this research is an analytical survey with a cross-sectional approach. The sample of this research is all women who come in pairs as data sources with 34 respondents with an accidental sampling technique. The results showed that of 34 respondents there were (76.5%) respondents experienced severe pain. Respondents with a high-risk age are (32.4%), and respondents with a low-risk age are (67.6%). Respondents with high parity (26.5%), respondents with low parity (73.5%), then respondents with anxiety (64.7%), and respondents without anxiety (35.3%). The results of the chi-square statistical test show that there is a significant relationship between age with a p-value of 0.007 < (0.05), there is a parity relationship with a p-value of 0.001 < (0.05), there is also a relationship between anxiety and pain intensity with a p-value 0.001 < (0.05). It is recommended for further researchers to develop and refine this research by using different variables and methods regarding labor pain in the first active phase. Keywords : Labor, Pain, Age, Parity, Anxiety